2023
DOI: 10.2217/fnl-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

Stroke severity among ischemic stroke patients with elevated diastolic blood pressure

Abstract: Aim: Understanding risk factors with elevated diastolic blood pressure (DBP) in acute ischemic stroke (AIS) is significant. Methods: Multivariable logistic regression was used to determine predictors of stroke severity in AIS patients, categorized by their DBP levels >80 mmHg and ≤80 mmHg. Results: AIS patients with DBP >80 mmHg that presents with a history of alcohol use (OR = 2.11, 95% CI: 1.116–3.988, p = 0.022), hypertension (OR = 1.572, 95% CI: 1.01–2.449, p = 0.035), and increasing heart rate (OR =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…20 Other studies, however, have found that diastolic blood pressure more than 80 mmHg is associated with poor outcomes in cases of ischemic stroke. 35,36 The majority of the study subjects (n = 32, n% = 80%) had systolic blood pressure > 140 mmHg or diastolic blood pressure > 90 mmHg when they arrived at the hospital. With these values, blood pressure can be categorized as stage 2 hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…20 Other studies, however, have found that diastolic blood pressure more than 80 mmHg is associated with poor outcomes in cases of ischemic stroke. 35,36 The majority of the study subjects (n = 32, n% = 80%) had systolic blood pressure > 140 mmHg or diastolic blood pressure > 90 mmHg when they arrived at the hospital. With these values, blood pressure can be categorized as stage 2 hypertension.…”
Section: Discussionmentioning
confidence: 99%